In defence of morphometric analysis of bone points - Turk, Ivan (Arheološki vestnik, 2005)
The paper is an answer to the criticism of morphometricanalysis of Early Upper Palaeolithic bone points. New resultson the typology and stratigraphicaly supported evolutionarytrends of bone and other points from Slovene palaeolithic sitesare presented